ASSOCIATIONS OF PLATINUM-GROUP MINERALS FROM THE ZOLOTAYA GOLD PLACER, PRIMORYE, RUSSIAN FAR EAST - Shcheka G.G.; Vrzhosek A.A.; Lehmann B.; Tolstykh N.D. (My University, 2004)
The platinum-group minerals (PGM) and chromite composition of the Zolotaya River gold placer, in the Russian Far East, indicate a genetic relationship to poorly exposed Late Permian dunite - hornblendite - gabbro intrusions of Uralian-Alaskan type. Ninety percent of the PGM grains studied consist of Pt-Fe alloy, typically with a rhodium content in the 1-2 wt.% range. Pt-bearing Os-Ir-Ru alloy occurs in three variants: (1) heterogeneous grains with an exsolution texture, (2) intergrowths of Os- Ir alloy with Pt-Fe alloy, and (3) homogeneous grains. Minerals of the erlichmanite-laurite series are relatively rare. Their composition varies from pure laurite through Os-bearing laurite to erlichmanite. Cooperite occurs in multiphase inclusions (in association with cuprorhodsite and chalcopyrite) in Pt-Fe alloy, and as a secondary rim (occasionally intergrown with platarsite and sperrylite) around Pt-Fe grains. Heterogeneous aggregates of Pt-Fe and Ru-Pt-Ir alloy have inclusions of arsenides of rhodium, iridium and ruthenium (cherepanovite, iridarsenite, ruthenarsenite) and a sulfarsenide-rich rim (irarsite).
Keywords: Pt–Fe alloy; platinum-group minerals; Uralian–Alaskan-type complex; gold-bearing placers; platinum-group elements; Primorye; Russia